Uma travessia pelo avesso das imagens - Santos, Mariana Borges dos (2021)
This dissertation is the beginning of elaborating questions that emerge singularly in a subjectivity and that propose themselves as collective, since they bring up experiences that cross a multiplicity of other bodies that share the same socio-cultural context. I call this elaboration crossing, without implying points of departure and arrival, because it is a continuous process that intends to constitute a body capable of inhabiting the announced and present ruins of a hegemonically western, colonial, patriarchal, racialized, anthropocentric, anthropocenic, globalized and capitalistic epistemology. The focus of this research points to two of the pillars that support this secular regime: the prevalence of vision as a way of apprehending reality and images as ways of capturing desire. This work proposes to map some of the subjectivity and desire policies that can occur in the different daily relationships with these images. What is going on inside out these relationships? The inside out, here, does not mean what is hidden behind the images, as one might suppose. When placing images as the plane of forms, the inside out is the plane of forces, both coexisting and coextensive in relations of mutual and reciprocal affectation. It is by creating sensitivity to sustain itself in the field of forces, that this text struggles to release, unload, detach, desubjectivate the forms that have expired, which depend on identification and prevent singularization. The text is composed of two parts: the first is an exercise of courage and approximation with this field of the sensitive where something announces to move; the second is made up of narrative lines in which the process of desubjectivation takes place in the form of conceptual characters who share, among themselves, the trait of indeterminacy. They are what-are-their-names (fulanas, beltranas and sicranas), in their existential universes, who indicate some of the ways of operating inherited from this colonial ruin and, also, other ways capable of causing it to collapse